AN Analysis of the causes of students disruptive behavior in classroom at elementary school level in tehsil Faisalabad city - Shahid, Hafiza Fariha; Choudhary, Khalid Mahmood; Ashraf, Ijaz; Usman, Muhammad; Afzal , Samreen (Journal of Pakistan Psychiatric Society, 2019)
Objective To analyze the causes of student’s disruptive behavior in classroom at elementary school level in tehsil Faisalabad, PakistanStudy designCross sectional research designPlace and duration of study The study was conducted at elementary schools of tehsil Faisalabad city Pakistan from oct 2017 to Nov 2018.Subjects and methodsElementary school students were served as study population. Sample of 84 respondents were selected by using simple random sampling technique. Questionnaire was used for collecting information about causes of student’s disruptive behavior in classroom.ResultsMajority (50.0%) of the respondents were agreed that students who are facing family problems and tension are more disruptive as compared to others. Most (33.3%) of the respondents were agreed that students behave disruptively when they are not under the control of the teacher.ConclusionIt was concluded that teachers and students in school’s think in a same way about the causes of disruptive classroom behavior. Both the groups think that larger class size, attention seeking from teachers, students’ emotional problems, teacher’s style of classroom management are the main causes of students’ disruptive classroom behavior.